Artemisinin Prevents Glutamate-Induced Neuronal Cell Death Via Akt Pathway Activation - Lin, Shao-Peng; Li, Wenjun; Winters, Ali; Liu, Ran; Yang, Shao-Hua (Frontiers in Cellular Neuroscience, 2018)
Artemisinin is an anti-malarial drug that has been in use for almost half century. Recently, novel biological effects of artemisinin on cancer, inflammation-related disorders, and cardiovascular disease were reported. However, neuroprotective actions of artemisinin against glutamate-induced oxidative stress have not been investigated. In the current study, we determined the effect of artemisinin against oxidative insult in HT-22 mouse hippocampal cell line. We found that pretreatment of artemisinin declined reactive oxygen species (ROS) production, attenuated the collapse of mitochondrial membrane potential induced by glutamate and rescued HT-22 cells from glutamate-induced cell death. Furthermore, our study demonstrated that artemisinin activated Akt/Bcl-2 signaling and that neuroprotective effect of artemisinin was blocked by Akt-specific inhibitor, MK2206. Taken together, our study indicated that artemisinin prevented neuronal HT-22 cell from glutamate-induced oxidative injury by activation of Akt signaling pathway.